Diversity, phylogenetic relationship and antibacterial potential of Bifidobacterium species isolated from raw milk production chain in Abidjan (Côte d'Ivoire) - Kouamé-Sina, S.M.; Dadie, A.; Makita, K.; Grace, Delia; Dje, M.; Taminiau, B.; Daube, G.; Bonfoh, Bassirou (2011)
The local dairy commodity, from farm to retail point, is informal and often escapes safety surveillance and results in high contamination of local milk by pathogens. The objective of this study was to determine the biodiversity of Bifidobacterium species in the informal dairy production chain in Abidjan and evaluate their potential antibacterial activity against pathogens. Bifidobacterium species were identified after sequencing of hsp60 genes. Results showed that Bifidobacterium were present in 9% of samples. Milkers' hands (14%) and cows’s udders (14%) were the most contaminated with Bifidobacterium. These isolates belong to five different species. Most Bifidobacterium isolated are Bifidobacterium minimum (53%) and Bifidobacterium pseudolongum subsp. Globosum (24.4%). The other strains are composed of one strain of Bifidobacterium thermophilum, Bifidobacterium thermacidophilum subsp. suis and Bifidobacterium magnum. The isolated Bifidobacterium species have antibacterial activities that are not related to bacteriocins production, but to organic acids production (65%), which exert in vitro inhibitory action against Listeria monocytogenes, Salmonella hadar and Salmonella typhimurium, Staphylococcus aureus, Escherichia coli O27 and Escherichia coli O157H7. However, ensuring milk safety along the local milk production chain requires implementation of good hygiene practices together with adapted technology, such as fermentation.